Comparative impacts of the COVID‐19 pandemic on work and employment—Why industrial relations institutions matter. Issue 2 (24th January 2023) - Dobbins, Tony; Johnstone, Stewart; Kahancová, Marta; Lamare, J. Ryan; Wilkinson, Adrian
Abstract: This introduction assesses the international impacts of the COVID‐19 pandemic on work and employment. It outlines conceptually why industrial relations institutions matter for shaping policy choices across different countries. This includes countries in the Global South that are not covered by conventional varieties of capitalism theories. An important focus is what IR institutions and policies played a protective role in the decommodification of labor during the pandemic, notably short‐time working (furlough) schemes, tripartite cooperative pacts, works councils, collective bargaining, and active labor market policies. IR institutions continue to matter, and the contributions in this Special Issue can inform future research.